Synergism therapeutic and immunoregulatory effects of Albendazole + rAd-mIL-28B against Echinococcosis in experiment-infected mice with protoscoleces. - Yan Zhang (Public Library of Science (PLoS), 2021)
The metacestode stage of Echinococcus granulosus can cause cystic echinococcosis (CE), which still widely occurs around the world. Since the early 1970s, benzimidazoles have been shown to inhibit the growth of cysts and used to treat CE. However, benzimidazoles are still ineffective in 20%-40% of cases. In order to explore the new agents against CE, we have investigated the therapeutic effect of the recombinant adenoviral vector expressing mouse IL-28B (rAd-mIL-28B) on protoscoleces-infected mice. In our study, we successfully established the model mice which infected with protoscoleces intraperitoneally. At 18 weeks post-infection, the mice received rAd-mIL-28B (1×107 PFU) weekly by intramuscular injection for 6 weeks. Compared with the untreated control (13.1 ± 2.2 g), there was a significant reduction in cysts wet weight in rAd-mIL-28B group (8.3 ± 3.5 g) (P < 0.05), especially in Albendazole (ABZ) + rAd-mIL-28B group (5.8 ± 1.4 g) (P < 0.01). We also observed the severe damage of the germinal layer and the laminated layer of cysts after treatment. rAd-mIL-28B group showed a prominent increase in the level of Th1 type cytokines (such as IFN-γ, IL-2 and TNF-α). Meanwhile, the frequency of Foxp3+ T cells was decreased in the rAd-mIL-28B group (4.83 ± 0.81%) and ABZ + rAd-mIL-28B group (4.60 ± 0.51%), comparing with the untreated group (8.13 ± 2.60%) (P < 0.05). In addition, compared with the untreated control (122.14 ± 81.09 pg/ml), the level of IFN-γ significantly increased in peritoneal fluid in the rAd-mIL-28B group (628.87 ± 467.16 pg/ml) (P < 0.05) and ABZ + rAd-mIL-28B group (999.76 ± 587.60 pg/ml) (P < 0.001). Taken together, it suggested that ABZ + IL-28B may be a potential therapeutic agent against CE.